The Creation of Dance From the Interpretation of the Rama Character in Ramayana Through Bravas and Rasa Theory - Phinitthanasarn, Nareerat; Charassri, Narapong (Thai Journal of East Asian Studies, 2019)
The purpose of this study is to create performance which is interpretative from the "Rama" character in Ramayana through Bhavas and Rasa theory. Ram’s characters were expressed emotionally and sentimentally which were attacked from various conditions as human beings. Thus, both Eastern and Western theories were applied by distinguishing situations “Bhavas” varying 9 sentiments―“Rasa”- love, anger, sadness, fear, wonder, amusement, heroism, and peace; as Psychoanalytic and Human behavioral theories. The concept of this performance is created by three approaches: composition, multiculturalism and postmodernism. The research found that there are the 9 – part performance with post-modernistic dance was not focused on narration, but exploration and adaptation processes. Which brings the concept of Minimalism to be applied to 8 forms of performance aspects: The play, The performers, The movement, The sound and music of the performance, The costumes, The space, The lighting and The equipment. Furthermore, dance’s beautifully national characteristics and audience’s involvement were presented, so new generations can easily learn moral conducts.